Iran’s internet blackout could worsen human toll of war, say rights groups - Down, Aisha; Parent, Deepa (The Guardian, 2026)
Experts say government’s shutdown means civilians are not seeing evacuation warnings before bombs hit
Keywords: Internet; Iran; Middle East and north Africa; US-Israel war on Iran; World news